Pengaruh Sop (Standar Operating Procedure) dan Penghargaan (Reward) Terhadap Kepuasan Karyawan Depertement Marketing PT. Karya Indah Multiguna - Arif Igo; Giharjo Giharjo (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of Standard Operating Procedure and awards on employees at PT. Karya Indah Multiguna. This study uses a quantitative descriptive method. The sampling technique in this study was a saturated sample involving 50 people. The data collection technique used a questionnaire, while the data analysis used Simple Linear Regression and Multiple Linear Regression. The results of this study indicate that there is a positive and significant effect between Standard Operating Procedure (X1) and Reward (X2) on employees (Y). Calculation results: 1) P-value (sign) <0.05 means that H0 is rejected and H1 is accepted, meaning that there is a Standard Operating Procedure (X1) on the influence of employees (Y) of 0.383 or 38.3%. 2) Obtained P-value (sign) <0.05, meaning that H0 is rejected and H1 is accepted, meaning that there is an influence between the Reward (X2) on the employee award (Y) of 0.641 or 64.1%. 3) Obtained Pvalue (sign) <0.05, meaning that H0 is rejected and H1 is accepted, meaning that there is an influence between Standard Operating Procedure (X1) and Reward (X2) on the increase in Employees (Y) of 0.693 or 69.3%. Thus it can be said that: simultaneously SOPs have influence and costs that affect employees.